Media Q and A at G20 Meeting, Brisbane, Australia, November 14, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses setting a clear target for growth. He is pleased with the focus on infrastructure. The World Bank, the Asian Development Bank, African Development Bank, and the Inter-American Development Bank plus others, together will supply about $100 billion in support for infrastructure. Kim fielded questions about the fight against Ebola, the proposal for a contingency fund to prevent future outbreaks, developing country expectations of the G20 summit, inequality, the Global Infrastructure Facility, and the China-US pact and climate change.